A Comment on "Income and Inequality in the Aztec Empire on the Eve of the Spanish Conquest" - Olle Hammar (Institute for Replication (I4R), 2025)
Alfani and Carballo (2023) estimate the levels of income inequality in the Aztec Empire around 1492, that is, before the Spanish conquest. Their main estimate finds that the Gini index was 50.4. They conclude that income inequality in the Aztec Empire was high even before the Spanish conquest, questioning to what extent today's high levels of economic inequality in Mexico can be explained by the Spanish conquest and extractive institutions imposed by the colonizers. First, I confirm that the main outcomes are computationally reproducible from the analysis data provided in the replication package. Second, I detect two inconsistencies with respect to the Kolmogorov-Smirnov test and the IV analysis, but after correcting for those I obtain qualitatively similar results. Third, I test the robustness reproducibility of the relationship between population density and per capita income through eleven different robustness tests, confirming a positive and statistically significant relationship but with large variation in the point estimates. Finally, I use these estimates as inputs for robustness measures of the main outcomes. On average, these robustness reproductions yield very similar results to those in the original paper. However, they also indicate large uncertainty about the exact estimates, for example, with Gini index estimates ranging between 38.8 and 65.6. As such, the conclusion that the level of income inequality was higher in the Aztec Empire than in modern Mexico does not appear to be a robust finding. The finding that it was more unequal than in contemporary United States, however, seems to be robust.
Keywords: 330